Effects of dominance and female presence on secondary sexual characteristics in male tufted capuchin monkeys (Sapajus apella). Issue 11 (30th March 2021) - Paukner, Annika; Slonecker, Emily M.; Wooddell, Lauren J.
Abstract: Alpha status may lead to physiological changes that enhance secondary sexual characteristics, which may serve as competitive signals to conspecific males, sexual signals to females, or possibly a combination of both. Here, we report measurements of secondary sexual characteristics in captive dominant and subordinate male tufted capuchin monkeys ( Sapajus apella ) with varying access to females. An adult male (who had previously been subordinate while housed with other males) was paired with an adult female. This male–female pair was introduced into a room that housed three other male–male pairs with stable hierarchy arrangements. We analyzed weight, body measurements, facial photographs, and hair cortisol before, during, and after introducing a female into the room. While there were no differences in weight or measurements between alphas and subordinates without physical access to the female prior to or during the female's presence, we found that direct access to the female resulted in dramatic changes in facial appearance, body size, and testicular volume in the male who was paired with her. Overall, we found little evidence to suggest that alpha males advertise their status within all‐male groups via sexual secondary characteristics. However, direct physical access to females appears to trigger the development of such characteristics in alpha males. It remains of continued interest to identify the endocrine mechanisms responsible for the development, and possible loss, of secondary sexual characteristics. Abstract : We investigated whether secondary sexual characteristics in male tufted capuchin monkeys were related to dominance rank or presence of a female. Our results suggest that the presence of a female can lead to the development of secondary sexual characteristics in alpha males, but that dominance status alone may not be sufficient.